2005
DOI: 10.1016/j.pain.2005.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiologic and quantitative sensory testing in the diagnosis of trigeminal neuropathy and neuropathic pain

Abstract: This study investigated the utility of neurophysiologic examination and thermal quantitative sensory testing (QST) in the diagnosis of trigeminal neuropathy and neuropathic pain. Fifty-eight patients (14 men), 34 with sensory deficit within the inferior alveolar nerve (IAN) and 24 within the lingual nerve (LN) distribution, were included. Twenty-six patients (45%) reported neuropathic pain. Patients underwent blink reflex (BR) test and thermal QST; sensory neurography was done to the IAN patients. Results of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(130 citation statements)
references
References 37 publications
7
113
0
4
Order By: Relevance
“…Thermal hypoaesthesia contralateral to the main pain area has been observed in patients with unilateral traumatic partial nerve injury [46] and with unilateral traumatic trigeminal neuropathy [36]. Bilateral hypoaesthesia may be mediated by peripheral nerve damage induced central plasticity [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal hypoaesthesia contralateral to the main pain area has been observed in patients with unilateral traumatic partial nerve injury [46] and with unilateral traumatic trigeminal neuropathy [36]. Bilateral hypoaesthesia may be mediated by peripheral nerve damage induced central plasticity [17].…”
Section: Discussionmentioning
confidence: 99%
“…One approach to assist in the interpretation of pain mechanisms underlying clinical pain presentations is the use of quantitative sensory testing (QST) [36,13,44,50,64]. To our 6 knowledge, no study has profiled patients with unilateral NSNAP comparable to our cohort, and only one study documented sensory abnormalities in patients with cervical radiculopathy [13].…”
Section: Introductionmentioning
confidence: 99%
“…Other reports [16,21] describe an incidence as high as 5% of neuropathic pain among patients who sustained peripheral trigeminal nerve injuries after sagittal split ramus osteotomy. Teerijoki-Oksa et al [22] prospectively followed 19 patients after BSSO surgery and found a 5% overall occurrence of neuropathic pain at 1-year follow-up, which is similar to the overall estimated incidence of neuropathic pain after traumatic and iatrogenic nerve injuries.…”
Section: Neuropathic Pain After Bilateral Sagittal Split Osteotomy Inmentioning
confidence: 98%
“…It has typical clinical features regardless of where in the body it occurs that aid in its diagnosis. For instance, neuropathic pain is often characterized as waxing and waning, and lancinating, and it may be accompanied by paresthesias, numbness, tingling, and shooting sensations 21, 22, 23, 24, 25, 26. Neuropathic pain also typically follows the distribution of one or more sensory nerves that are damaged or inflamed.…”
Section: Mechanisms Of Orofacial Painmentioning
confidence: 99%
“…Sensory changes are sometimes also observed during clinical testing of PHN, including hyperalgesia and/or allodynia. Although some cases present with a clear history of nerve damage (e.g., due to dental procedure or other insult), the actual cause of the neuropathy often remains unknown and secondary causes such as autoimmune, malignancy, or infection could be typically considered 22, 27, 34…”
Section: Mechanisms Of Orofacial Painmentioning
confidence: 99%